Granule size distribution for a multi-chamber fluidized-bed melt granulator: modeling and validation using process measurement data - Bertin, Diego Esteban (2013)
In this work, a steady-state model of a multi-chamber fluidized-bed granulator used for urea production is developed and validated. To this aim, mass, energy and population balances are solved for all the fluidized beds. Regarding the population balance equation (PBE), pure coating or the combined mechanisms of coating and elutriation are taken into account. Both PBE formulations are analytically solved and a new solution methodology is proposed to handle inlet solid streams distributed in different size grids and to minimize the solution errors propagation expected when a set of PBEs in series has to be solved. By comparison with experimental data, it is found that the model including coating and elutriation gives a better representation of the particles size distribution with respect to the results found when pure coating is assumed. Besides, the results indicate that the fines are removed almost completely in the first and second chambers, being the amount of fines in the subsequent chambers negligible.